An approach combining the integral equation method with a generalized image technique for modeling incabin radio wave propagation. (27th March 2019) - Zhao, Wei‐Jiang; Liu, En‐Xiao; Wang, Binfang; Gao, Si‐Ping; Png, Ching Eng
Abstract: An approach that combines the integral equation (IE) method with a generalized image technique (GIT) is proposed for modeling radio wave propagation inside an electrically large and imperfectly conducting closed environment. The electric current distribution on a transmit antenna solved with a method of moment procedure is expressed as a weighted sum of basis functions. Each basis function with a small dimension is thought as a subtransmitter. The GIT is introduced to compute the single and multiple reflections by imperfectly conducting walls due to the radiation from these subtransmitters. The proposed approach can be applied to predict the radio wave propagation from a transmitter in the vicinity of an electrically large environment. Its validity is demonstrated through some numerical examples where full‐wave results are available.